Consequences of not Working Sixteen Months After a Plant Closing - Burke, Ronald (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1985)
This paper examines the consequences of being unemployed sixteen months after the closing ofthe Canadian Admiral plant in Cambridge, Ontario in November 1981.